Between craft and class : skilled workers and factory politics in the United States and Britain, 1890-1922 - Haydu, Jeffrey (Berkeley : University of California Press, 1988)
Between Craft and Class provides an incisive new look at workers' responses to the momentous economic changes surrounding them in the early years of the twentieth century. In this work, Haydu focuses on the reaction of skilled metal workers to new production methods that threatened time-honored craft traditions. He finds that the workers' responses to industrial change varied--some defended the status quo, while others agreed to trade customary rules fo.
Includes bibliographical references (pages 277-295) and index.
Print version record.
JSTOR
Keywords: Working class -- Political activity -- United States -- History; Working class -- Political activity -- Great Britain -- History; Artisans -- United States -- History; Artisans -- Great Britain -- History; Social classes -- United States -- History; Social classes -- Great Britain -- History; Travailleurs -- Activité politique -- États-Unis -- Histoire; Travailleurs -- Activité politique -- Grande-Bretagne -- Histoire; Artisans -- États-Unis -- Histoire; Artisans -- Grande-Bretagne -- Histoire; Classes sociales -- États-Unis -- Histoire; Classes sociales -- Grande-Bretagne -- Histoire; POLITICAL SCIENCE -- Political Process -- Political Advocacy; HISTORY / United States / General; Artisans; Social classes; Working class -- Political activity; Great Britain; United States; Facharbeiter; Unternehmenspolitik; Großbritannien; USA; Geschoold personeel; Bedrijfsbeleid; Geschichte (1890-1922); Sozialgeschichte 1890-1922.; History